2012
DOI: 10.1155/2012/529178
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Ferroresonance Limiter for Potential Transformers

Abstract: The ferroresonance or nonlinear resonance is a complex phenomenon, which may cause overvoltage in the electrical power system and endangers the system reliability and operation. The ability to predict the ferroresonance in the transformer depends on the accuracy of the transformer model used. In this paper, the effect of the new suggested ferroresonance limiter on the control of the chaotic ferroresonance and duration of chaotic transients in a potential transformer including nonlinear core losses is studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…However, with electronic or tuned circuits, the damping becomes effective only for the designed frequency. The various analyses of the literature revealed that the mitigation circuit damps the oscillations along with its own limitations (Ben et al , 1999; Kong and Ahoui, 2014; Tahir et al , 2013; Pattanapakdee and Banmongkol, 2007; Hamid et al , 2012; Hamid, 2012; Wenxima et al , 2014). The memristor emulator is designed as the load for the mitigation of ferroresonance.…”
Section: Experimentationmentioning
confidence: 99%
“…However, with electronic or tuned circuits, the damping becomes effective only for the designed frequency. The various analyses of the literature revealed that the mitigation circuit damps the oscillations along with its own limitations (Ben et al , 1999; Kong and Ahoui, 2014; Tahir et al , 2013; Pattanapakdee and Banmongkol, 2007; Hamid et al , 2012; Hamid, 2012; Wenxima et al , 2014). The memristor emulator is designed as the load for the mitigation of ferroresonance.…”
Section: Experimentationmentioning
confidence: 99%
“…Ferroresonance has occurred if CB and disconnector D S2 are opened, disconnector D S1 is closed and power system experiences no-load or lightly load conditions. In this model, the magnetisation current is modelled by two terms seventh-order polynomial, which has been obtained and introduced previously in [5,7,8,19,21] as…”
Section: Power System Modellingmentioning
confidence: 99%
“…Ferroresonance has occurred if CB and disconnector D S 2 are opened, disconnector D S 1 is closed and power system experiences no‐load or lightly load conditions. In this model, the magnetisation current is modelled by two terms seventh‐order polynomial, which has been obtained and introduced previously in [5, 7, 8, 19, 21] as inormalL=aλ+bλ7, where, λ = Nφ , N is the number of VT coil turns and per unit value of coefficient a is 3.42 and b is 0.41 [5]. In this case, the power system equivalent circuit is a ferroresonance circuit as shown in Fig.…”
Section: Power System Modellingmentioning
confidence: 99%
See 2 more Smart Citations